Implementasi Nilai-Nilai Profil Pelajar Pancasila dalam Pembelajaran Bahasa Indonesia pada Kurikulum Merdeka di SMA Negeri 1 Praya - Rohimatun Sodiah; Siti Rohana Hariana Intiana; Pipit Aprilia Susanti (Mataram University, 2026)
This study aims to describe the implementation of the values of the Pancasila Student Profile in Indonesian language learning and to identify the obstacles encountered in its implementation at SMA Negeri 1 Praya. This study uses a descriptive qualitative approach. Data were obtained through observation, interviews, and document studies. Data sources in this study include tenth-grade Indonesian language teachers, learning activities in the classroom, and learning documents such as teaching modules. The results of the study show that the implementation of the values of the Pancasila Student Profile in Indonesian language learning has been carried out well. This implementation is seen in learning activities from the preliminary activities, main activities, to closing activities. The six dimensions of the Pancasila Student Profile have been implemented through various learning activities such as group discussions, presentations, reflections, as well as individual and group assignments. However, in practice, there are still several obstacles, namely the lack of learning interest among some students, the low responsibility of some students in completing assignments, and not all students actively participating in group work activities.